Value chain of pangas and tilapia in Bangladesh: Value chain of pangas and tilapia (Journal of the Bangladesh Agricultural University, 2018)
The study assessed pangas and tilapia value chain, and analyze the internal and external governance of the market actors at different levels. Two hundred samples (100 for each of pangas and tilapia fish) were included in the study from selected areas of Bangladesh. A combination of descriptive statistics and mathematical analysis were used to analyze the data. GAMM analysis was used to address the actors and their functions, product flow, information flow and governance of pangas and tilapia value chain. The study reveals that among all the actors, processors added the highest value and farmers followed it. The internal and external governance issues followed by different actors could be ranked as average, which reveals the improvement issue through intervention from respective authorities. SWOT analysis indicated high demand for pangas and tilapia in domestic and international markets, inadequate market infrastructure and increasing cost of feed as major strength, weakness and threat, respectively. The study recommended that good governance should be ensured from the production point to consumer along all the actors of value chain. Government should take step about monitoring the feed quality and improvement of pangas and tilapia value chain governance. Moreover, DoF, BFRI and NGOs should play the assigned role to train up the chain actors and provide extension services in order to explore the export potential of pangas and tilapia fishes in Bangladesh.J. Bangladesh Agril. Univ. 16(3): 503–512, December 2018